Carbon nanotube reinforced composite flexible graphite plate and preparation method thereof

CN122930945APending Publication Date: 2026-10-16GUANGDONG YUNTAO HYDROGEN ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611381701.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]本发明所要解决的技术问题是提供一种碳纳米管增强复合柔性石墨极板及其制备方法,旨在解决复合石墨极板中碳纳米管以及树脂分布不均导致极板性能下降的问题

Benefits of technology

[0009] On the other hand, by immersing the composite graphite substrate in the resin solution in step S4 and then impregnating it under vacuum and pressure, the resin is uniformly penetrated into the graphite matrix in the form of a molecularly dispersed solution under vacuum-pressure drive. This solves the technical problem of local resin agglomeration caused by direct dry mixing of resin powder and graphite particles in the prior art. Thus, it achieves the technical effect of uniform resin coating and filling and improving the conductivity, airtightness and mechanical properties of the composite flexible graphite electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930945A_ABST
    Figure CN122930945A_ABST
Patent Text Reader

Abstract

This application belongs to the field of fuel cell electrode technology and discloses a carbon nanotube-reinforced composite flexible graphite electrode and its preparation method. The preparation method includes: ionizing the oxygen-containing functional groups on the surface of expanded graphite by alkaline solution impregnation to form negatively charged expanded graphite; introducing oxygen-containing functional groups such as carboxyl and hydroxyl groups on the surface of carbon nanotubes through Fenton oxidation treatment, and making the carbon nanotubes positively charged through amine salt adsorption; adding the negatively charged expanded graphite and positively charged carbon nanotubes into an alcohol solution and using vacuum / pressure impregnation to obtain a composite powder, and then rolling the composite powder to obtain a composite graphite substrate; immersing the composite graphite substrate in a resin solution and then penetrating it into the graphite matrix through liquid-phase impregnation by vacuum and pressure impregnation. The composite flexible graphite electrode prepared by the above method can effectively improve the dispersion of internal carbon nanotubes and resin, thereby improving the electrical and mechanical properties of the composite flexible graphite electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of fuel cell electrode technology, specifically to a carbon nanotube-reinforced composite flexible graphite electrode and its preparation method. Background Technology

[0002] The electrode plate is a core functional component of a proton exchange membrane fuel cell (PEMFC), playing crucial roles in reactant gas transport, current collection, heat transfer, and battery sealing. Its performance directly affects the fuel cell's output efficiency, operational stability, and lifespan. Because the electrode plate must operate in a high-humidity, acidic, and electrochemically reactive environment for extended periods, it must possess excellent electrical conductivity, airtightness, mechanical strength, and resistance to electrochemical corrosion. Currently, fuel cell electrode plates mainly include pure graphite electrode plates, metal electrode plates, and composite graphite electrode plates. Pure graphite electrode plates offer good electrical conductivity and corrosion resistance, but suffer from brittleness, insufficient mechanical strength, and high processing costs. Metal electrode plates, while possessing high strength and good formability, are prone to corrosion and passivation in the fuel cell's operating environment. In contrast, composite graphite electrode plates combine advantages in electrical conductivity, corrosion resistance, and formability, making them a significant development direction for fuel cell electrode plates.

[0003] However, in the existing process of preparing composite graphite electrodes, conductive reinforcing materials such as carbon nanotubes are usually introduced into the graphite matrix to improve the conductivity of the electrode. However, due to the large specific surface area and high surface energy of carbon nanotubes, they are prone to agglomeration and entanglement during mixing with graphite powder. This makes it difficult for carbon nanotubes to be evenly distributed within the graphite matrix, resulting in the formation of conductive filler aggregates in local areas, while other areas lack sufficient conductive paths, making it impossible to construct a continuous and stable conductive network. At the same time, the agglomerated carbon nanotubes also cause interfacial defects, reducing the bonding strength between them and the graphite and resin matrix, making it difficult to fully exert their reinforcing effect.

[0004] Furthermore, in the preparation of composite graphite electrodes, the resin, as a binder phase, needs to be uniformly distributed between the graphite particles to achieve particle connection and pore filling. However, existing technologies typically involve directly mixing and pressing resin powder with the particles, which easily leads to localized resin enrichment, i.e., resin agglomeration. This results in some areas having excessively high resin content, hindering direct contact between graphite particles and reducing conductivity; while other areas have insufficient resin content, leading to pore defects and reducing the density and airtightness of the plate. Simultaneously, resin agglomeration also causes uneven internal structure of the electrode, easily leading to interfacial stress concentration during long-term cyclic operation, causing crack propagation, and reducing the mechanical stability and service life of the electrode. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a carbon nanotube-reinforced composite flexible graphite electrode plate and its preparation method, aiming to solve the problem of uneven distribution of carbon nanotubes and resin in the composite graphite electrode plate leading to a decrease in electrode plate performance.

[0006] To address the aforementioned technical problems, a method for preparing a carbon nanotube-reinforced composite flexible graphite electrode is proposed, the method comprising the following steps: S1. Expand the flake graphite to obtain expanded graphite, then immerse the expanded graphite in an alkaline solution and filter it to obtain negatively charged expanded graphite. S2. Carbon nanotubes are added to Fenton oxidation solution for oxidation treatment to obtain modified carbon nanotubes. Then, the modified carbon nanotubes are added to an aqueous solution containing amine salt for surface treatment and filtered to obtain positively charged carbon nanotubes. The Fenton oxidation solution contains ferrous ions and hydrogen peroxide. S3. Negatively charged expanded graphite and positively charged carbon nanotubes are added to an alcohol solution, ultrasonically dispersed, vacuum / pressure impregnated, filtered, washed with deionized water, and dried to obtain a composite powder. The composite powder is then rolled to obtain a composite graphite substrate. S4. Add the resin to an organic solvent, heat to dissolve, and obtain a resin solution. Then add the composite graphite substrate to the resin solution, vacuum, pressurize and impregnate, dry, hot press and cool to obtain a carbon nanotube-reinforced composite flexible graphite electrode.

[0007] In addition, a carbon nanotube-reinforced composite flexible graphite electrode plate is provided, which is prepared by the above-described method for preparing a carbon nanotube-reinforced composite flexible graphite electrode plate.

[0008] As can be seen from the above technical solutions, the exemplary embodiments disclosed herein possess at least the following advantages and positive effects: On the one hand, the alkaline solution wetting in step S1 ionizes the oxygen-containing functional groups on the surface of expanded graphite, forming negatively charged graphite pore walls. On the other hand, the Fenton oxidation treatment in step S2 introduces carboxyl and hydroxyl groups onto the surface of carbon nanotubes, and the amine salt adsorption process allows the carbon nanotubes to carry a positive charge. These techniques create electrostatic repulsion between the modified carbon nanotubes due to their shared positive charge, reducing the probability of contact between them and preventing entanglement and aggregation during mixing. Simultaneously, during the alcohol solution dispersion in step S3, the positive charge on the surface of the modified carbon nanotubes interacts with the negative charge on the surface of the expanded graphite pore walls through electrostatic adsorption, causing the carbon nanotubes to migrate directionally from a free-dispersed state to the interlayer and pore structure of the expanded graphite sheets. Furthermore, the vacuum / pressure impregnation process further promotes the migration of carbon nanotubes. The carbon nanotubes are pre-positioned and fixed within the pores. Subsequently, deionized water washing and neutralization remove adsorbed amine salts and residual ions from the expanded graphite surface, reducing the surface charge density of the composite powder and minimizing the adverse effects of residual ions on the conductivity of the composite flexible graphite electrode. Simultaneously, the carboxyl and hydroxyl groups on the surface of the oxidized carbon nanotubes form hydrogen bonds and interfacial bonding forces with the oxygen-containing active sites on the surface of the expanded graphite. During subsequent drying and rolling processes, the interfacial bonding between the carbon nanotubes and the graphite matrix is ​​further enhanced, allowing the carbon nanotubes to be stably embedded within the graphite pore structure. This solves the problem of carbon nanotubes easily agglomerating and failing to form a continuous conductive network in existing technologies, thereby achieving the technical effect of improving the conductivity, mechanical properties, and structural stability of the composite graphite electrode.

[0009] On the other hand, by immersing the composite graphite substrate in the resin solution in step S4 and then impregnating it under vacuum and pressure, the resin is uniformly penetrated into the graphite matrix in the form of a molecularly dispersed solution under vacuum-pressure drive. This solves the technical problem of local resin agglomeration caused by direct dry mixing of resin powder and graphite particles in the prior art. Thus, it achieves the technical effect of uniform resin coating and filling and improving the conductivity, airtightness and mechanical properties of the composite flexible graphite electrode. Attached Figure Description

[0010] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this disclosure and, together with the description, serve to explain the principles of this disclosure. It is obvious that the drawings described below are merely some embodiments of this disclosure, and those skilled in the art can obtain other drawings based on these drawings without any inventive effort. In the drawings: Figure 1 This is a schematic diagram of a method for preparing a carbon nanotube-reinforced composite flexible graphite electrode in one embodiment; Figure 2 This is a schematic diagram of step S1 in the preparation method of a carbon nanotube-reinforced composite flexible graphite electrode in one embodiment; Figure 3 This is a schematic diagram of step S2 in the preparation method of carbon nanotube-reinforced composite flexible graphite electrode in one embodiment; Figure 4 This is a schematic diagram of step S3 in the preparation method of carbon nanotube-reinforced composite flexible graphite electrode in one embodiment; Figure 5 This is a schematic diagram of step S4 in the preparation method of a carbon nanotube-reinforced composite flexible graphite electrode in one embodiment; Figure 6 This is a schematic diagram of the structure of the composite powder; Figure 7 This is a diagram showing the orientation distribution of carbon nanotubes. Figure 8 This is a schematic diagram of the composite graphite substrate. Detailed Implementation

[0011] Exemplary embodiments will now be described more fully with reference to the accompanying drawings. However, these exemplary embodiments can be implemented in many forms and should not be construed as limited to the examples set forth herein; rather, these embodiments are provided so that this disclosure will be more thorough and complete, and will fully convey the concept of the exemplary embodiments to those skilled in the art.

[0012] Furthermore, the described features or characteristics may be combined in any suitable manner in one or more embodiments. Numerous specific details are provided in the following description to give a thorough understanding of embodiments of this disclosure. However, those skilled in the art will recognize that the technical solutions of this disclosure may be practiced without one or more of the specific details, or other methods, steps, etc. may be employed. In other instances, well-known methods, implementations, or operations are not shown or described in detail to avoid obscuring various aspects of this disclosure.

[0013] The flowcharts shown in the accompanying drawings are merely illustrative and do not necessarily include all content and operations / steps, nor do they necessarily have to be performed in the described order. For example, some operations / steps can be broken down, while others can be combined or partially combined; therefore, the actual execution order may change depending on the specific circumstances.

[0014] Please refer to Figure 1 This invention proposes a method for preparing a carbon nanotube-reinforced composite flexible graphite electrode, the method comprising the following steps: S1. Expand the flake graphite to obtain expanded graphite, then immerse the expanded graphite in an alkaline solution and filter to obtain negatively charged expanded graphite.

[0015] In step S1, the flake graphite is flake graphite with a purity of ≥99.98%, and the alkaline solution is an aqueous solution containing 1~2wt% alkaline substances, including at least one of ammonia, sodium hydroxide, sodium carbonate, and sodium bicarbonate.

[0016] In step S1, an alkaline solution containing 1-2 wt% alkaline substances is used to impregnate the expanded graphite, causing partial deprotonation of oxygen-containing functional groups such as hydroxyl and carboxyl groups on the surface of the expanded graphite. This increases the negative potential of the expanded graphite surface, forming a negatively charged active interface. This enhances the electrostatic adsorption between the expanded graphite and the subsequently positively modified carbon nanotubes, allowing the modified carbon nanotubes to enter the interlamellar gaps and pore structure of the expanded graphite under the guidance of electrostatic action. It also reduces the mutual entanglement and aggregation of carbon nanotubes caused by van der Waals interactions, promoting the uniform dispersion of carbon nanotubes in the expanded graphite matrix.

[0017] Step S1 includes: S1.1 Place the flake graphite in a reaction vessel, heat it to 850~950℃ for expansion treatment, cool it, and sieve it to obtain expanded graphite with a particle size of 100~500μm.

[0018] Flake graphite is placed in a reaction vessel and heated to 850~950℃ for expansion treatment. The high temperature causes the intercalation material between the graphite layers to rapidly vaporize and decompose, generating strong expansion pressure that forcibly pushes apart the graphite flakes, forming expanded graphite with a rich worm-like pore structure. This temperature range can ensure that the intercalation material decomposes and expands fully while avoiding excessive oxidation and ablation of the graphite. Combined with subsequent cooling and sieving operations, expanded graphite powder with uniform particle size, suitable porosity, well-developed pores, and retaining the complete graphite lattice structure can be obtained.

[0019] S1.2. Immerse expanded graphite in an alkaline solution, stir at 50~60℃ for 1.5~2.5h, filter to obtain negatively charged expanded graphite, wherein the mass ratio of expanded graphite to alkaline solution is 1:(8~10).

[0020] Expanded graphite is immersed in an alkaline solution and stirred at 50-60°C for 1.5-2.5 hours, utilizing the OH- ions in the alkaline solution. - The oxygen-containing functional groups such as carboxyl and hydroxyl groups on the edge of the pore walls of expanded graphite undergo deprotonation, causing the oxygen-containing functional groups on the surface of expanded graphite to become negatively charged, thereby increasing the negative potential of the expanded graphite particles and forming a negatively charged interface structure. At the same time, by controlling the mass ratio of expanded graphite to alkaline solution to 1: (8~10), the alkaline solution can fully wet and penetrate into the internal pores of expanded graphite, improving the uniformity of surface potential regulation in each region.

[0021] S2. Carbon nanotubes are added to Fenton oxidation solution for oxidation treatment to obtain modified carbon nanotubes. Then, the modified carbon nanotubes are added to an aqueous solution containing amine salt for surface treatment and filtered to obtain positively charged carbon nanotubes. The Fenton oxidation solution contains ferrous ions and hydrogen peroxide.

[0022] In step S2, the length of the carbon nanotubes is 5-15 mm, the Fenton oxidation solution is an aqueous solution containing 0.01-0.05 mol / L sulfuric acid, 0.01-0.03 mol / L ferrous ions, and 2.4-3.6 mol / L hydrogen peroxide, and the amine salt includes at least one of ethylamine hydrochloride, ammonium chloride, propylamine hydrochloride, and ethylenediamine dihydrochloride.

[0023] In step S2, Fenton oxidation solution is used to oxidize carbon nanotubes, introducing oxygen-containing functional groups such as carboxyl and hydroxyl groups onto the surface of carbon nanotubes, thereby increasing the polarity and the number of active sites on the surface of carbon nanotubes. Subsequently, the electrostatic adsorption between the protonated ammonium groups formed by the amine salt in the aqueous solution and the oxygen-containing functional groups on the surface of carbon nanotubes is utilized to load the amine salt component onto the surface of carbon nanotubes, adjusting the interfacial charge state of the carbon nanotube surface to make it positively charged, thereby enhancing the electrostatic repulsion between carbon nanotubes, reducing the mutual entanglement and aggregation of carbon nanotubes caused by van der Waals effects, and improving their stability in subsequent mixing and dispersion processes.

[0024] Step S2 includes: S2.1 Add carbon nanotubes to Fenton oxidation solution, stir and oxidize at 55~70℃ for 2~3h, filter and wash with deionized water until the pH of the filtrate is 6.5~7.5, and no red color appears when potassium thiocyanate solution is added to the filtrate, indicating that the washing is complete, and modified carbon nanotubes are obtained, wherein the mass ratio of carbon nanotubes to Fenton oxidation solution is 1:(20~30).

[0025] The surface of carbon nanotubes is oxidized using the Fenton oxidation reaction, through the use of Fenton reagent (Fe). 2+ The oxidation reaction with H₂O₂ generates highly oxidizing hydroxyl radicals, which attack the sidewalls and end defects of carbon nanotubes, introducing oxygen-containing functional groups such as carboxyl (-COOH) and hydroxyl (-OH) groups onto their surface. Simultaneously, controlling the degree of oxidation avoids excessive damage to the carbon nanotube structure, ensuring that its conductivity is not compromised. Subsequent washing with deionized water until the filtrate is neutral, and the Fe²⁺ content is detected using potassium thiocyanate solution. 3+ Has it been washed clean (if it contains Fe)? 3+ (If it turns red), it ensures that the obtained modified carbon nanotubes are pure and free of metal ion residues, thus avoiding contamination of the electrode performance.

[0026] S2.2 Add the modified carbon nanotubes to an aqueous solution containing amine salt, ultrasonically disperse at 30~40℃ for 60~120min, filter to obtain positively charged carbon nanotubes, wherein the mass ratio of modified carbon nanotubes to aqueous solution is 1:(8~10), and the concentration of amine salt in aqueous solution is 0.05~0.5mol / L.

[0027] After adding the amine salt aqueous solution in step S2.2, the protonated amino cations generated by the dissociation of the amine salt diffuse fully to the surface of the carbon nanotubes under ultrasonication. They are adsorbed around oxygen-containing functional groups such as carboxylate and hydroxyl groups through electrostatic adsorption and hydrogen bonding, forming an adsorption layer mainly composed of protonated amino groups on the surface of the carbon nanotubes. The surface zeta potential gradually changes from negative to positive, eventually exhibiting a stable positive charge. S3. Negatively charged expanded graphite and positively charged carbon nanotubes are added to an alcohol solution, ultrasonically dispersed, vacuum / pressure impregnated, filtered, washed with deionized water, and dried to obtain a composite powder. The composite powder is then rolled to obtain a composite graphite substrate.

[0028] The alcohol solution in step S3 includes at least one of ethanol, isopropanol, and n-butanol.

[0029] Negatively charged expanded graphite and positively charged carbon nanotubes were co-dispersed in an alcohol solution using ultrasound. The low surface tension and good wetting properties of the alcohol solution reduced the tendency for particle aggregation. Simultaneously, the electrostatic attraction between the negatively charged expanded graphite and the positively charged carbon nanotubes facilitated the directional adsorption of carbon nanotubes into the expanded graphite sheets and pore structure. Subsequently, a vacuum / pressure impregnation process was combined to further promote the entry of carbon nanotubes into the internal pores of the expanded graphite under pressure difference, improving the uniformity of carbon nanotube distribution in the graphite matrix. After washing with deionized water, ions and amine salt residues introduced during electrostatic assembly were removed to avoid ionic impurities affecting the conductivity of the electrode. Drying and rolling further stabilized the carbon nanotubes between the graphite sheets, forming a uniform and continuous conductive framework and a stable pore structure, providing uniform impregnation channels and an interfacial basis for subsequent resin impregnation.

[0030] Step S3 includes: S3.1 Add negatively charged expanded graphite and positively charged carbon nanotubes to an alcohol solution and ultrasonically disperse for 30-50 min to obtain a suspension. The mass ratio of negatively charged expanded graphite and positively charged carbon nanotubes to the alcohol solution is (94-96):(1-3):(500-700).

[0031] Negatively charged expanded graphite and positively charged carbon nanotubes were added to an alcohol solution and ultrasonically dispersed. The low surface tension and excellent wetting properties of the alcohol solution improved the wetting effect of the expanded graphite and carbon nanotubes. At the same time, the low dielectric constant of the alcohol solution weakened the ionic solvation effect, making the electrostatic attraction between the positive and negative charges more obvious. This promoted the directional adsorption of positively charged carbon nanotubes on the surface and near the pores of negatively charged expanded graphite. Under the action of ultrasonic cavitation, uniform dispersion was achieved, resulting in a stable suspension.

[0032] S3.2 Place the suspension in a vacuum impregnation tank, first evacuate to below 10 kPa and maintain for 20-30 min, then pressurize to 0.8-1.3 MPa and maintain for 40-60 min, filter to obtain pre-composite powder.

[0033] First, the suspension is evacuated to allow the air in the expanded graphite sheets and pores to escape completely. Then, pressure is applied to create a pressure difference driving force, which promotes the positively charged carbon nanotubes to enter the internal pores and interlayer gaps of the expanded graphite along with the alcohol solution. Under the action of electrostatic adsorption, they are stably attached to the surface of the pore wall. Subsequently, the unadsorbed carbon nanotubes and excess dispersion medium are removed by filtration to obtain a pre-composite powder with uniform carbon nanotube distribution and sufficient embedding.

[0034] S3.3. The pre-composite powder is added to a weak alkaline solution for neutralization and washed with deionized water until the conductivity of the filtrate is ≤2μS / cm to obtain a composite precipitate. The composite precipitate is then heated to 80~100℃ and dried for 2~3h to obtain a composite powder. The weak alkaline solution is an aqueous solution containing a weak alkaline substance with a mass concentration of 0.5~5wt%, and the weak alkaline substance includes at least one of ammonia, ammonium bicarbonate, and ammonium carbonate.

[0035] The pre-composite powder is neutralized by adding it to a weak alkaline solution with a mass concentration of 0.5~5wt%. The OH- in the weak alkaline solution... - It can undergo acid-base neutralization reactions with protonated amine salts on the surface of carbon nanotubes, promoting the gradual dissociation of electrostatic bonds between the amine salts and oxygen-containing functional groups on the surface of expanded graphite. This effectively eliminates the positive and negative potential points originally used to promote electrostatic assembly, avoiding interference from residual charges and ionic components on the electron conduction path of the electrode plates. Subsequently, it is washed with deionized water until the conductivity of the filtrate is ≤2μS / cm to further remove free amine salts, acid radicals, and other soluble ions. During the drying process at 80~100℃, as moisture is gradually removed, the oxygen-containing functional groups such as hydroxyl and carboxyl groups dissociated on the surface of modified carbon nanotubes form more stable hydrogen bonds and interfacial interactions with the oxygen-containing structures on the surface of expanded graphite. This enhances the bonding stability between carbon nanotubes and graphite sheets, allowing carbon nanotubes to be firmly embedded in the porous structure of expanded graphite. This reduces the migration and detachment of carbon nanotubes during subsequent rolling and resin impregnation, improving the structural stability of the composite powder.

[0036] S3.4. The composite powder is fed into a double roller press for rolling to obtain a composite graphite substrate, wherein the thickness of the composite graphite substrate is 0.25~0.65mm.

[0037] The composite powder is subjected to double-roll pressing, which utilizes the compression and shearing effect generated by the roll pressing to promote the tight bonding between the expanded graphite sheets, allowing carbon nanotubes to be further embedded in the gaps between the graphite sheets and form a continuous conductive path. At the same time, it reduces the internal porosity of the composite powder, improves the density of the substrate, and obtains a composite graphite substrate with uniform thickness and stable structure.

[0038] In one embodiment, step S3.1 further includes: S3.1 Add negatively charged expanded graphite and lubricant to an alcohol solution, stir and disperse to obtain a lubricating liquid, then add positively charged carbon nanotubes to the lubricating liquid and ultrasonically disperse for 30-50 minutes to obtain a suspension. The mass ratio of negatively charged expanded graphite, positively charged carbon nanotubes, lubricant and alcohol solution is (94-96):(1-3):(0.5-2):(500-700). The lubricant is polytetrafluoroethylene powder.

[0039] Negatively charged expanded graphite and polytetrafluoroethylene (PTFE) powder were first dispersed in an alcohol solution, allowing the PTFE powder to be uniformly distributed as solid particles on the surface and between the expanded graphite sheets. The excellent lubricating properties of PTFE reduced the frictional resistance between the graphite sheets, minimizing the recombination and agglomeration of the expanded graphite during dispersion. Subsequently, positively charged carbon nanotubes were added for ultrasonic dispersion. The PTFE particles acted as a spatial isolation medium, reducing the probability of direct contact between carbon nanotubes and between carbon nanotubes and graphite sheets, preventing entanglement and aggregation of carbon nanotubes. At the same time, the pore structure of the graphite remained open, promoting the uniform adsorption and dispersion of positively charged carbon nanotubes in the negatively charged expanded graphite.

[0040] S4. Add the resin to an organic solvent, heat to dissolve, and obtain a resin solution. Then add the composite graphite substrate to the resin solution, vacuum, pressurize and impregnate, dry, hot press and cool to obtain a carbon nanotube-reinforced composite flexible graphite electrode.

[0041] In step S4, the resin is polyvinylidene fluoride resin and / or phenolic resin, and the organic solvent includes at least one of N-methylpyrrolidone, dimethylformamide, dimethylacetamide, dimethyl sulfoxide, tetrahydrofuran, and acetone.

[0042] The resin is dissolved in an organic solvent to form a homogeneous resin solution, transforming the resin from solid particles into a liquid impregnation system with good flowability. Combined with vacuum suction and pressure impregnation, the gas resistance in the internal pores of the composite graphite substrate is reduced, promoting the uniform penetration of the resin solution along the gaps and pore structure of the graphite sheets. This allows the resin to fully fill the micropores inside the graphite matrix and form a continuous and uniform binder phase. At the same time, during the hot pressing process, the resin further melts and flows, uniformly coating the carbon nanotubes and graphite skeleton, enhancing the interfacial bonding between the carbon nanotubes and the graphite matrix, and reducing interfacial defects caused by local resin enrichment and uneven resin distribution.

[0043] Step S4 includes: S4.1 Add the resin to an organic solvent and stir at 40~80℃ to dissolve it, thereby obtaining a resin solution, wherein the mass concentration of the resin in the resin solution is 17~21wt%.

[0044] The resin is added to an organic solvent and heated and stirred to allow the resin molecular chains to fully expand and dissolve uniformly, forming a stable and homogeneous resin solution. By controlling the resin mass concentration to 17~21wt%, the resin solution has suitable viscosity and fluidity, which can reduce the penetration resistance of the resin solution during impregnation and ensure that the resin is uniformly distributed inside the composite graphite substrate after impregnation, thereby improving the resin filling effect.

[0045] S4.2 Add the composite graphite substrate to the resin solution, first evacuate to below 10 kPa and maintain for 20~30 min, then pressurize to 0.8~1.3 MPa and maintain for 40~60 min to remove the substrate and obtain the pre-fabricated graphite electrode plate. The mass ratio of the composite graphite electrode plate to the resin solution is 1:(2~5).

[0046] A vacuum / pressure impregnation process is used to process the composite graphite substrate. First, air in the pores inside the substrate is removed by vacuuming to reduce the resistance to resin solution entering the pores. Then, external pressure is used to promote the resin solution to fully penetrate along the gaps between graphite layers and the microporous structure, so that the resin uniformly fills the pores inside the composite graphite substrate and makes full contact with carbon nanotubes and graphite skeleton. By controlling the ratio of composite graphite substrate to resin solution, sufficient resin wetting is ensured, local resin enrichment and pore defects are reduced, and a prefabricated graphite electrode plate with uniform resin distribution and stable structure is obtained.

[0047] S4.3. Heat the pre-made graphite electrode plate to 100~120℃ and dry it for 2~3 hours. Put it into the mold and keep it at 180~210℃ and 10~14MPa for 60~90 minutes. Cool, demold, and cut to obtain carbon nanotube reinforced composite flexible graphite electrode plate.

[0048] The pre-fabricated graphite electrode plate is dried and hot-pressed to allow the organic solvent in the resin solution to fully evaporate. Under high temperature and high pressure conditions, the resin melts, flows, and solidifies uniformly, further filling the micropores inside the graphite matrix and enhancing the interfacial bonding between graphite sheets and carbon nanotubes. At the same time, the hot pressing effect improves the overall density of the composite flexible graphite electrode plate, reduces internal pore defects, and obtains a carbon nanotube-reinforced composite flexible graphite electrode plate with stable structure, continuous conductive network, and excellent mechanical properties.

[0049] In one embodiment, step S4.2 further includes: S4.2 Place the composite graphite substrate in a vacuum oven and preheat it at 60~80℃ for 20~40min to obtain a preheated substrate. Then transfer the preheated substrate to a resin solution at 40~80℃ for 1~3min, evacuate it to below 10kPa, maintain it for 20~30min, then pressurize it to 0.8~1.3MPa and maintain it for 40~60min to remove it and obtain a pre-fabricated graphite electrode plate. The mass ratio of the composite graphite electrode plate to the resin solution is 1:(2~5), and the temperature of the preheated substrate is higher than the temperature of the resin solution.

[0050] The composite graphite substrate is preheated to 60-80°C and then rapidly transferred to a resin solution at a temperature lower than that of the substrate for impregnation. This causes the residual gas in the pores of the substrate to expand and be released in advance due to heat. During the subsequent vacuuming process, the amount of residual gas inside the pores is reduced, which can more effectively reduce the pore pressure during the vacuum stage and avoid the reverse resistance formed by the compression of residual gas during the resin entry process. At the same time, the preheating treatment avoids the problem of rapid increase in resin viscosity due to the sudden drop in temperature at the initial contact between the graphite substrate and the resin solution. This allows the resin to maintain good fluidity and wetting ability under vacuum suction and pressure, further improving the uniformity of resin filling the gaps and micropore structure of graphite sheets, reducing internal pore defects, and improving the density and structural stability of the prefabricated graphite electrode.

[0051] In addition, a carbon nanotube-reinforced composite flexible graphite electrode plate is provided, which is prepared by the above-described method for preparing a carbon nanotube-reinforced composite flexible graphite electrode plate.

[0052] The carbon nanotube-reinforced composite flexible graphite electrode has a volume conductivity ≥292 S / cm and a surface resistivity ≤4.7 mΩ·cm. 2 Contact resistance ≤ 6.9 mΩ·cm 2 Flexural strength ≥ 76.3 MPa, hydrogen permeability ≤ 2.7 × 10⁻⁶ -9 cm 3 / (cm 2 (·s·Pa), helium permeability ≤2.1×10 -9 cm 3 / (cm 2 Corrosion current density ≤0.58 μA / cm² (·s·Pa). 2 .

[0053] For example, the present invention provides the following specific embodiments to illustrate the specific preparation method: Example 1: S1.1 Place flake graphite with a purity ≥ 99.98% in a reaction vessel, heat to 900℃ for expansion treatment, cool and sieve to obtain expanded graphite with a particle size of 300μm; S1.2. Immerse expanded graphite in an alkaline solution, stir at 55°C for 2 hours, filter to obtain negatively charged expanded graphite, wherein the mass ratio of expanded graphite to alkaline solution is 1:9, and the alkaline solution is an aqueous solution with a sodium hydroxide concentration of 1.5wt%. S2.1 Add carbon nanotubes to Fenton oxidation solution, stir and oxidize at 62℃ for 2.5h, filter and wash with deionized water until the pH of the filtrate is 7.0, and no red color appears when potassium thiocyanate solution is added to the filtrate, indicating that the washing is complete, and modified carbon nanotubes are obtained. The mass ratio of carbon nanotubes to Fenton oxidation solution is 1:25. Fenton oxidation solution is an aqueous solution containing 0.03mol / L sulfuric acid, 0.02mol / L ferrous ions and 3.0mol / L hydrogen peroxide. S2.2 Add the modified carbon nanotubes to an aqueous solution containing ethylamine hydrochloride, ultrasonically disperse at 35°C for 90 min, filter, and obtain positively charged carbon nanotubes. The mass ratio of modified carbon nanotubes to aqueous solution is 1:9, and the concentration of ethylamine hydrochloride in the aqueous solution is 0.3 mol / L. S3.1 Add negatively charged expanded graphite and positively charged carbon nanotubes to ethanol and disperse by ultrasonication for 40 min to obtain a suspension, wherein the mass ratio of negatively charged expanded graphite and positively charged carbon nanotubes to ethanol is 95:2:600. S3.2 Place the suspension in a vacuum impregnation tank, first evacuate to below 10 kPa and maintain for 25 min, then pressurize to 1.0 MPa and maintain for 50 min, filter to obtain pre-composite powder; S3.3 Add the pre-composite powder to a weak alkaline solution for neutralization, and wash with deionized water until the conductivity of the filtrate is ≤2μS / cm to obtain a composite precipitate. Then heat the composite precipitate to 90℃ and dry for 2.5h to obtain the composite powder. The weak alkaline solution is an aqueous solution containing 2wt% ammonia. S3.4. The composite powder is fed into a double roller press for rolling to obtain a composite graphite substrate, wherein the thickness of the composite graphite substrate is 0.45mm. S4.1 Add polyvinylidene fluoride resin to N-methylpyrrolidone and stir at 60°C to dissolve, thereby obtaining a resin solution, wherein the mass concentration of polyvinylidene fluoride resin in the resin solution is 19 wt%. S4.2 Add the composite graphite substrate to the resin solution, first evacuate to below 10 kPa and maintain for 25 min, then pressurize to 1.0 MPa and maintain for 50 min to remove the substrate and obtain the pre-fabricated graphite electrode plate. The mass ratio of the composite graphite electrode plate to the resin solution is 1:3.5. S4.3. Heat the pre-made graphite electrode plate to 110℃ and dry it for 2.5h. Put it into the mold and keep it at 195℃ and 12MPa pressure for 75min. Cool, demold, and cut to obtain carbon nanotube reinforced composite flexible graphite electrode plate.

[0054] Example 2: S1.1 Place flake graphite with a purity ≥ 99.98% in a reaction vessel, heat to 900℃ for expansion treatment, cool and sieve to obtain expanded graphite with a particle size of 300μm; S1.2. Immerse expanded graphite in an alkaline solution, stir at 55°C for 2 hours, filter to obtain negatively charged expanded graphite, wherein the mass ratio of expanded graphite to alkaline solution is 1:9, and the alkaline solution is an aqueous solution with a sodium hydroxide concentration of 1.5wt%. S2.1 Add carbon nanotubes to Fenton oxidation solution, stir and oxidize at 62℃ for 2.5h, filter and wash with deionized water until the pH of the filtrate is 7.0, and no red color appears when potassium thiocyanate solution is added to the filtrate, indicating that the washing is complete, and modified carbon nanotubes are obtained. The mass ratio of carbon nanotubes to Fenton oxidation solution is 1:25. Fenton oxidation solution is an aqueous solution containing 0.03mol / L sulfuric acid, 0.02mol / L ferrous ions and 3.0mol / L hydrogen peroxide. S2.2 Add the modified carbon nanotubes to an aqueous solution containing ethylamine hydrochloride, ultrasonically disperse at 35°C for 90 min, filter, and obtain positively charged carbon nanotubes. The mass ratio of modified carbon nanotubes to aqueous solution is 1:9, and the concentration of ethylamine hydrochloride in the aqueous solution is 0.3 mol / L. S3.1 Negatively charged expanded graphite and lubricant polytetrafluoroethylene powder are added to ethanol, stirred and dispersed to obtain a lubricating liquid. Then, positively charged carbon nanotubes are added to the lubricating liquid and ultrasonically dispersed for 30-50 minutes to obtain a suspension. The mass ratio of negatively charged expanded graphite, positively charged carbon nanotubes, polytetrafluoroethylene powder and ethanol is 95:2:1:600. S3.2 Place the suspension in a vacuum impregnation tank, first evacuate to below 10 kPa and maintain for 25 min, then pressurize to 1.0 MPa and maintain for 50 min, filter to obtain pre-composite powder; S3.3 Add the pre-composite powder to a weak alkaline solution for neutralization, and wash with deionized water until the conductivity of the filtrate is ≤2μS / cm to obtain a composite precipitate. Then heat the composite precipitate to 90℃ and dry for 2.5h to obtain the composite powder. The weak alkaline solution is an aqueous solution containing 2wt% ammonia. S3.4. The composite powder is fed into a double roller press for rolling to obtain a composite graphite substrate, wherein the thickness of the composite graphite substrate is 0.45mm. S4.1 Add polyvinylidene fluoride resin to N-methylpyrrolidone and stir at 60°C to dissolve, thereby obtaining a resin solution, wherein the mass concentration of polyvinylidene fluoride resin in the resin solution is 19 wt%. S4.2 Add the composite graphite substrate to the resin solution, first evacuate to below 10 kPa and maintain for 25 min, then pressurize to 1.0 MPa and maintain for 50 min to remove the substrate and obtain the pre-fabricated graphite electrode plate. The mass ratio of the composite graphite electrode plate to the resin solution is 1:3.5. S4.3. Heat the pre-made graphite electrode plate to 110℃ and dry it for 2.5h. Put it into the mold and keep it at 195℃ and 12MPa pressure for 75min. Cool, demold, and cut to obtain carbon nanotube reinforced composite flexible graphite electrode plate.

[0055] It is basically the same as Example 1, except that in step S3.1, lubricant polytetrafluoroethylene powder is also added.

[0056] Example 3: S1.1 Place flake graphite with a purity ≥ 99.98% in a reaction vessel, heat to 900℃ for expansion treatment, cool and sieve to obtain expanded graphite with a particle size of 300μm; S1.2. Immerse expanded graphite in an alkaline solution, stir at 55°C for 2 hours, filter to obtain negatively charged expanded graphite, wherein the mass ratio of expanded graphite to alkaline solution is 1:9, and the alkaline solution is an aqueous solution with a sodium hydroxide concentration of 1.5wt%. S2.1 Add carbon nanotubes to Fenton oxidation solution, stir and oxidize at 62℃ for 2.5h, filter and wash with deionized water until the pH of the filtrate is 7.0, and no red color appears when potassium thiocyanate solution is added to the filtrate, indicating that the washing is complete, and modified carbon nanotubes are obtained. The mass ratio of carbon nanotubes to Fenton oxidation solution is 1:25. Fenton oxidation solution is an aqueous solution containing 0.03mol / L sulfuric acid, 0.02mol / L ferrous ions and 3.0mol / L hydrogen peroxide. S2.2 Add the modified carbon nanotubes to an aqueous solution containing ethylamine hydrochloride, ultrasonically disperse at 35°C for 90 min, filter, and obtain positively charged carbon nanotubes. The mass ratio of modified carbon nanotubes to aqueous solution is 1:9, and the concentration of ethylamine hydrochloride in the aqueous solution is 0.3 mol / L. S3.1 Add negatively charged expanded graphite and positively charged carbon nanotubes to ethanol and disperse by ultrasonication for 40 min to obtain a suspension, wherein the mass ratio of negatively charged expanded graphite and positively charged carbon nanotubes to ethanol is 95:2:600. S3.2 Place the suspension in a vacuum impregnation tank, first evacuate to below 10 kPa and maintain for 25 min, then pressurize to 1.0 MPa and maintain for 50 min, filter to obtain pre-composite powder; S3.3 Add the pre-composite powder to a weak alkaline solution for neutralization, and wash with deionized water until the conductivity of the filtrate is ≤2μS / cm to obtain a composite precipitate. Then heat the composite precipitate to 90℃ and dry for 2.5h to obtain the composite powder. The weak alkaline solution is an aqueous solution containing 2wt% ammonia. S3.4. The composite powder is fed into a double roller press for rolling to obtain a composite graphite substrate, wherein the thickness of the composite graphite substrate is 0.45mm. S4.1 Add polyvinylidene fluoride resin to N-methylpyrrolidone and stir at 60°C to dissolve, thereby obtaining a resin solution, wherein the mass concentration of polyvinylidene fluoride resin in the resin solution is 19 wt%. S4.2 Place the composite graphite substrate in a vacuum oven and preheat it at 80°C for 30 minutes to obtain a preheated substrate. Then transfer the preheated substrate to a resin solution at 60°C for 2 minutes, evacuate it to below 10 kPa, maintain it for 25 minutes, then pressurize it to 1.0 MPa, maintain it for 50 minutes, and take it out to obtain a pre-fabricated graphite electrode plate. The mass ratio of the composite graphite electrode plate to the resin solution is 1:3.5. S4.3. Heat the pre-made graphite electrode plate to 110℃ and dry it for 2.5h. Put it into the mold and keep it at 195℃ and 12MPa pressure for 75min. Cool, demold, and cut to obtain carbon nanotube reinforced composite flexible graphite electrode plate.

[0057] The process is basically the same as in Example 1, except that in step S4.2, the composite graphite electrode plate is preheated and the temperature of the composite graphite electrode plate is higher than the temperature of the resin solution.

[0058] Example 4: S1.1 Place flake graphite with a purity ≥ 99.98% in a reaction vessel, heat to 900℃ for expansion treatment, cool and sieve to obtain expanded graphite with a particle size of 300μm; S1.2. Immerse expanded graphite in an alkaline solution, stir at 55°C for 2 hours, filter to obtain negatively charged expanded graphite, wherein the mass ratio of expanded graphite to alkaline solution is 1:9, and the alkaline solution is an aqueous solution with a sodium hydroxide concentration of 1.5wt%. S2.1 Add carbon nanotubes to Fenton oxidation solution, stir and oxidize at 62℃ for 2.5h, filter and wash with deionized water until the pH of the filtrate is 7.0, and no red color appears when potassium thiocyanate solution is added to the filtrate, indicating that the washing is complete, and modified carbon nanotubes are obtained. The mass ratio of carbon nanotubes to Fenton oxidation solution is 1:25. Fenton oxidation solution is an aqueous solution containing 0.03mol / L sulfuric acid, 0.02mol / L ferrous ions and 3.0mol / L hydrogen peroxide. S2.2 Add the modified carbon nanotubes to an aqueous solution containing ethylamine hydrochloride, ultrasonically disperse at 35°C for 90 min, filter, and obtain positively charged carbon nanotubes. The mass ratio of modified carbon nanotubes to aqueous solution is 1:9, and the concentration of ethylamine hydrochloride in the aqueous solution is 0.3 mol / L. S3.1 Add negatively charged expanded graphite and positively charged carbon nanotubes to ethanol and disperse by ultrasonication for 40 min to obtain a suspension, wherein the mass ratio of negatively charged expanded graphite and positively charged carbon nanotubes to ethanol is 95:2:600. S3.2 Place the suspension in a vacuum impregnation tank, first evacuate to below 10 kPa and maintain for 25 min, then pressurize to 1.0 MPa and maintain for 50 min, filter to obtain pre-composite powder; S3.3 Add the pre-composite powder to a weak alkaline solution for neutralization, and wash with deionized water until the conductivity of the filtrate is ≤2μS / cm to obtain a composite precipitate. Then heat the composite precipitate to 90℃ and dry for 2.5h to obtain the composite powder. The weak alkaline solution is an aqueous solution containing 2wt% ammonia. S3.4. The composite powder is fed into a double roller press for rolling to obtain a composite graphite substrate, wherein the thickness of the composite graphite substrate is 0.45mm. S4.1. Phenolic resin is added to N-methylpyrrolidone and stirred at 60°C to dissolve, thereby obtaining a resin solution, wherein the mass concentration of phenolic resin in the resin solution is 19 wt%. S4.2 Add the composite graphite substrate to the resin solution, first evacuate to below 10 kPa and maintain for 25 min, then pressurize to 1.0 MPa and maintain for 50 min to remove the substrate and obtain the pre-fabricated graphite electrode plate. The mass ratio of the composite graphite electrode plate to the resin solution is 1:3.5. S4.3. Heat the pre-made graphite electrode plate to 110℃ and dry it for 2.5h. Put it into the mold and keep it at 195℃ and 12MPa pressure for 75min. Cool, demold, and cut to obtain carbon nanotube reinforced composite flexible graphite electrode plate.

[0059] It is basically the same as Example 1, except that the resin used in step S4.1 is phenolic resin.

[0060] Comparative Example 1: S1. Place flake graphite with a purity of ≥99.98% in a reaction vessel, heat to 900℃ for expansion treatment, cool and sieve to obtain expanded graphite with a particle size of 300μm; S2.1 Add carbon nanotubes to Fenton oxidation solution, stir and oxidize at 62℃ for 2.5h, filter and wash with deionized water until the pH of the filtrate is 7.0, and no red color appears when potassium thiocyanate solution is added to the filtrate, indicating that the washing is complete, and modified carbon nanotubes are obtained. The mass ratio of carbon nanotubes to Fenton oxidation solution is 1:25. Fenton oxidation solution is an aqueous solution containing 0.03mol / L sulfuric acid, 0.02mol / L ferrous ions and 3.0mol / L hydrogen peroxide. S2.2 Add the modified carbon nanotubes to an aqueous solution containing ethylamine hydrochloride, ultrasonically disperse at 35°C for 90 min, filter, and obtain positively charged carbon nanotubes. The mass ratio of modified carbon nanotubes to aqueous solution is 1:9, and the concentration of ethylamine hydrochloride in the aqueous solution is 0.3 mol / L. S3.1 Add expanded graphite and positively charged carbon nanotubes to ethanol and ultrasonically disperse for 40 min to obtain a suspension, wherein the mass ratio of expanded graphite, positively charged carbon nanotubes to ethanol is 95:2:600. S3.2 Place the suspension in a vacuum impregnation tank, first evacuate to below 10 kPa and maintain for 25 min, then pressurize to 1.0 MPa and maintain for 50 min, filter to obtain pre-composite powder; S3.3 Add the pre-composite powder to a weak alkaline solution for neutralization, and wash with deionized water until the conductivity of the filtrate is ≤2μS / cm to obtain a composite precipitate. Then heat the composite precipitate to 90℃ and dry for 2.5h to obtain the composite powder. The weak alkaline solution is an aqueous solution containing 2wt% ammonia. S3.4. The composite powder is fed into a double roller press for rolling to obtain a composite graphite substrate, wherein the thickness of the composite graphite substrate is 0.45mm. S4.1 Add polyvinylidene fluoride resin to N-methylpyrrolidone and stir at 60°C to dissolve, thereby obtaining a resin solution, wherein the mass concentration of polyvinylidene fluoride resin in the resin solution is 19 wt%. S4.2 Add the composite graphite substrate to the resin solution, first evacuate to below 10 kPa and maintain for 25 min, then pressurize to 1.0 MPa and maintain for 50 min to remove the substrate and obtain the pre-fabricated graphite electrode plate. The mass ratio of the composite graphite electrode plate to the resin solution is 1:3.5. S4.3. Heat the pre-made graphite electrode plate to 110℃ and dry it for 2.5h. Put it into the mold and keep it at 195℃ and 12MPa pressure for 75min. Cool, demold, and cut to obtain carbon nanotube reinforced composite flexible graphite electrode plate.

[0061] It is basically the same as Example 1, except that the expanded graphite in step S1 is not treated with an alkaline solution.

[0062] Comparative Example 2: S1.1 Place flake graphite with a purity ≥ 99.98% in a reaction vessel, heat to 900℃ for expansion treatment, cool and sieve to obtain expanded graphite with a particle size of 300μm; S1.2. Immerse expanded graphite in an alkaline solution, stir at 55°C for 2 hours, and filter to obtain negatively charged expanded graphite. The mass ratio of expanded graphite to alkaline solution is 1:9, and the alkaline solution is a 1.5 wt% aqueous solution of sodium hydroxide. S2.1 Add negatively charged expanded graphite and carbon nanotubes to ethanol and ultrasonically disperse for 40 min to obtain a suspension, wherein the mass ratio of negatively charged expanded graphite and carbon nanotubes to ethanol is 95:2:600. S2.2 Place the suspension in a vacuum impregnation tank, first evacuate to below 10 kPa and maintain for 25 min, then pressurize to 1.0 MPa and maintain for 50 min, filter to obtain pre-composite powder; S2.3. The pre-composite powder is added to a weak alkaline solution for neutralization and washed with deionized water until the conductivity of the filtrate is ≤2μS / cm to obtain a composite precipitate. The composite precipitate is then heated to 90℃ and dried for 2.5h to obtain a composite powder. The weak alkaline solution is an aqueous solution containing 2wt% ammonia. S2.4. The composite powder is fed into a double roller press for rolling to obtain a composite graphite substrate, wherein the thickness of the composite graphite substrate is 0.45 mm. S3.1 Add polyvinylidene fluoride resin to N-methylpyrrolidone and stir at 60°C to dissolve, thereby obtaining a resin solution, wherein the mass concentration of polyvinylidene fluoride resin in the resin solution is 19 wt%. S3.2 Add the composite graphite substrate to the resin solution, first evacuate to below 10 kPa and maintain for 25 min, then pressurize to 1.0 MPa and maintain for 50 min to remove the substrate and obtain the pre-fabricated graphite electrode plate. The mass ratio of the composite graphite electrode plate to the resin solution is 1:3.5. S3.3. Heat the pre-made graphite electrode plate to 110℃ and dry it for 2.5h. Put it into the mold and keep it at 195℃ and 12MPa pressure for 75min. Cool, demold, and cut to obtain carbon nanotube reinforced composite flexible graphite electrode plate.

[0063] It is basically the same as Example 1, except that ordinary carbon nanotubes are used instead of positively charged carbon nanotubes.

[0064] Comparative Example 3: S1.1 Place flake graphite with a purity ≥ 99.98% in a reaction vessel, heat to 900℃ for expansion treatment, cool and sieve to obtain expanded graphite with a particle size of 300μm; S1.2. Immerse expanded graphite in an alkaline solution, stir at 55°C for 2 hours, filter to obtain negatively charged expanded graphite, wherein the mass ratio of expanded graphite to alkaline solution is 1:9, and the alkaline solution is an aqueous solution with a sodium hydroxide concentration of 1.5wt%. S2.1 Add carbon nanotubes to Fenton oxidation solution, stir and oxidize at 62℃ for 2.5h, filter and wash with deionized water until the pH of the filtrate is 7.0, and no red color appears when potassium thiocyanate solution is added to the filtrate, indicating that the washing is complete, and modified carbon nanotubes are obtained. The mass ratio of carbon nanotubes to Fenton oxidation solution is 1:25. Fenton oxidation solution is an aqueous solution containing 0.03mol / L sulfuric acid, 0.02mol / L ferrous ions and 3.0mol / L hydrogen peroxide. S2.2 Add the modified carbon nanotubes to an aqueous solution containing ethylamine hydrochloride, ultrasonically disperse at 35°C for 90 min, filter, and obtain positively charged carbon nanotubes. The mass ratio of modified carbon nanotubes to aqueous solution is 1:9, and the concentration of ethylamine hydrochloride in the aqueous solution is 0.3 mol / L. S3.1 Add negatively charged expanded graphite and positively charged carbon nanotubes to ethanol, ultrasonically disperse for 40 min, stir at 600 rpm for 50 min, filter to obtain pre-composite powder, wherein the mass ratio of negatively charged expanded graphite, positively charged carbon nanotubes to ethanol is 95:2:600. S3.2 Add the pre-composite powder to a weak alkaline solution for neutralization, and wash with deionized water until the conductivity of the filtrate is ≤2μS / cm to obtain a composite precipitate. Then heat the composite precipitate to 90℃ and dry it for 2.5h to obtain the composite powder. The weak alkaline solution is an aqueous solution containing 2wt% ammonia. S3.4. The composite powder is fed into a double roller press for rolling to obtain a composite graphite substrate, wherein the thickness of the composite graphite substrate is 0.45mm. S4.1 Add polyvinylidene fluoride resin to N-methylpyrrolidone and stir at 60°C to dissolve, thereby obtaining a resin solution, wherein the mass concentration of polyvinylidene fluoride resin in the resin solution is 19 wt%. S4.2 Add the composite graphite substrate to the resin solution, first evacuate to below 10 kPa and maintain for 25 min, then pressurize to 1.0 MPa and maintain for 50 min to remove the substrate and obtain the pre-fabricated graphite electrode plate. The mass ratio of the composite graphite electrode plate to the resin solution is 1:3.5. S4.3. Heat the pre-made graphite electrode plate to 110℃ and dry it for 2.5h. Put it into the mold and keep it at 195℃ and 12MPa pressure for 75min. Cool, demold, and cut to obtain carbon nanotube reinforced composite flexible graphite electrode plate.

[0065] The method is basically the same as in Example 1, except that in step S3, a conventional stirring method is used instead of a vacuum / pressure impregnation method.

[0066] Comparative Example 4: S1.1 Place flake graphite with a purity ≥ 99.98% in a reaction vessel, heat to 900℃ for expansion treatment, cool and sieve to obtain expanded graphite with a particle size of 300μm; S1.2. Immerse expanded graphite in an alkaline solution, stir at 55°C for 2 hours, filter to obtain negatively charged expanded graphite, wherein the mass ratio of expanded graphite to alkaline solution is 1:9, and the alkaline solution is an aqueous solution with a sodium hydroxide concentration of 1.5wt%. S2.1 Add carbon nanotubes to Fenton oxidation solution, stir and oxidize at 62℃ for 2.5h, filter and wash with deionized water until the pH of the filtrate is 7.0, and no red color appears when potassium thiocyanate solution is added to the filtrate, indicating that the washing is complete, and modified carbon nanotubes are obtained. The mass ratio of carbon nanotubes to Fenton oxidation solution is 1:25. Fenton oxidation solution is an aqueous solution containing 0.03mol / L sulfuric acid, 0.02mol / L ferrous ions and 3.0mol / L hydrogen peroxide. S2.2 Add the modified carbon nanotubes to an aqueous solution containing ethylamine hydrochloride, ultrasonically disperse at 35°C for 90 min, filter, and obtain positively charged carbon nanotubes. The mass ratio of modified carbon nanotubes to aqueous solution is 1:9, and the concentration of ethylamine hydrochloride in the aqueous solution is 0.3 mol / L. S3.1 Add negatively charged expanded graphite and positively charged carbon nanotubes to ethanol and disperse by ultrasonication for 40 min to obtain a suspension, wherein the mass ratio of negatively charged expanded graphite and positively charged carbon nanotubes to ethanol is 95:2:600. S3.2 Place the suspension in a vacuum impregnation tank, first evacuate to below 10 kPa and maintain for 25 min, then pressurize to 1.0 MPa and maintain for 50 min, filter to obtain pre-composite powder; S3.3 Add the pre-composite powder to a weak alkaline solution for neutralization, and wash with deionized water until the conductivity of the filtrate is ≤2μS / cm to obtain a composite precipitate. Then heat the composite precipitate to 90℃ and dry for 2.5h to obtain the composite powder. The weak alkaline solution is an aqueous solution containing 2wt% ammonia. S3.4. The composite powder is fed into a double roller press for rolling to obtain a composite graphite substrate, wherein the thickness of the composite graphite substrate is 0.45 mm. S4.1 Add polyvinylidene fluoride resin to N-methylpyrrolidone and stir at 60°C to dissolve, thereby obtaining a resin solution, wherein the mass concentration of polyvinylidene fluoride resin in the resin solution is 19 wt%. S4.2 Add the composite graphite substrate to the resin solution, stir at 600 rpm for 70 min and remove to obtain the pre-fabricated graphite electrode plate, wherein the mass ratio of the composite graphite electrode plate to the resin solution is 1:3.5. S4.3. Heat the pre-made graphite electrode plate to 110℃ and dry it for 2.5h. Put it into the mold and keep it at 195℃ and 12MPa pressure for 75min. Cool, demold, and cut to obtain carbon nanotube reinforced composite flexible graphite electrode plate.

[0067] The method is basically the same as in Example 1, except that in step S4, a conventional stirring method is used instead of a vacuum / pressure impregnation method.

[0068] Comparative Example 5: S1.1 Place flake graphite with a purity ≥ 99.98% in a reaction vessel, heat to 900℃ for expansion treatment, cool and sieve to obtain expanded graphite with a particle size of 300μm; S1.2. Immerse expanded graphite in an alkaline solution, stir at 55°C for 2 hours, filter to obtain negatively charged expanded graphite, wherein the mass ratio of expanded graphite to alkaline solution is 1:9, and the alkaline solution is an aqueous solution with a sodium hydroxide concentration of 1.5wt%. S2.1 Add carbon nanotubes to Fenton oxidation solution, stir and oxidize at 62℃ for 2.5h, filter and wash with deionized water until the pH of the filtrate is 7.0, and no red color appears when potassium thiocyanate solution is added to the filtrate, indicating that the washing is complete, and modified carbon nanotubes are obtained. The mass ratio of carbon nanotubes to Fenton oxidation solution is 1:25. Fenton oxidation solution is an aqueous solution containing 0.03mol / L sulfuric acid, 0.02mol / L ferrous ions and 3.0mol / L hydrogen peroxide. S2.2 Add the modified carbon nanotubes to an aqueous solution containing ethylamine hydrochloride, ultrasonically disperse at 35°C for 90 min, filter, and obtain positively charged carbon nanotubes. The mass ratio of modified carbon nanotubes to aqueous solution is 1:9, and the concentration of ethylamine hydrochloride in the aqueous solution is 0.3 mol / L. S3.1 Add negatively charged expanded graphite and positively charged carbon nanotubes to ethanol and ultrasonically disperse for 40 min to obtain a suspension, wherein the mass ratio of negatively charged expanded graphite and positively charged carbon nanotubes to ethanol is 95:5:600. S3.2 Place the suspension in a vacuum impregnation tank, first evacuate to below 10 kPa and maintain for 25 min, then pressurize to 1.0 MPa and maintain for 50 min, filter to obtain pre-composite powder; S3.3 Add the pre-composite powder to a weak alkaline solution for neutralization, and wash with deionized water until the conductivity of the filtrate is ≤2μS / cm to obtain a composite precipitate. Then heat the composite precipitate to 90℃ and dry for 2.5h to obtain the composite powder. The weak alkaline solution is an aqueous solution containing 2wt% ammonia. S3.4. The composite powder is fed into a double roller press for rolling to obtain a composite graphite substrate, wherein the thickness of the composite graphite substrate is 0.45 mm. S4.1 Add polyvinylidene fluoride resin to N-methylpyrrolidone and stir at 60°C to dissolve, thereby obtaining a resin solution, wherein the mass concentration of polyvinylidene fluoride resin in the resin solution is 19 wt%. S4.2 Add the composite graphite substrate to the resin solution, first evacuate to below 10 kPa and maintain for 25 min, then pressurize to 1.0 MPa and maintain for 50 min to remove the substrate and obtain the pre-fabricated graphite electrode plate. The mass ratio of the composite graphite electrode plate to the resin solution is 1:3.5. S4.3. Heat the pre-made graphite electrode plate to 110℃ and dry it for 2.5h. Put it into the mold and keep it at 195℃ and 12MPa pressure for 75min. Cool, demold, and cut to obtain carbon nanotube reinforced composite flexible graphite electrode plate.

[0069] The process is basically the same as in Example 1, except that the mass ratio of negatively charged expanded graphite, positively charged carbon nanotubes and ethanol in step S3.1 is 95:5:600.

[0070] Comparative Example 6: Flake graphite with a purity of ≥99.98% was placed in a reaction vessel and heated to 900℃ for expansion treatment. After cooling and sieving, expanded graphite with a particle size of 300μm was obtained. Expanded graphite, carbon nanotubes and polyvinylidene fluoride resin were mixed and stirred to obtain a mixture. The mixture was then loaded into a mold and kept at 195℃ and 12MPa pressure for 75min. After cooling, demolding and cutting, carbon nanotube-reinforced composite flexible graphite electrode plates were obtained.

[0071] Performance testing: Density: The density of the composite flexible graphite electrode was tested using the 25℃ hydrostatic weighing method (Archimedes' principle). Before testing, the sample was processed into a regular-sized specimen and dried to constant weight at 105℃. After cooling to room temperature, the mass m1 of the sample in air was measured. Subsequently, the sample was completely immersed in 25℃ deionized water to remove surface air bubbles, and the apparent mass m2 of the sample in water was measured. The volume of the sample was calculated based on the volume of liquid displaced by the sample, and the density was determined using the formula ρ = m1 / (m1-m2) × ρ. 水 Calculate the material density.

[0072] Volumetric conductivity and surface resistivity: The volumetric conductivity and surface resistivity of the composite flexible graphite electrode were tested using a DC four-probe method. Before testing, the sample surface was polished to ensure a smooth and clean testing area. The four probes were vertically pressed onto the sample surface, with the probe pressing pressure controlled at 0.5 N. A stable test current was applied to the outer probes using a constant current source, and the voltage difference between the inner probes was measured using a voltmeter. The surface resistivity of the material was calculated based on the current, voltage, and probe spacing, and then the volumetric conductivity was obtained by combining this with the sample thickness.

[0073] Contact resistance: The interfacial contact resistance was tested using a composite flexible graphite electrode / gas diffusion layer combination. The prepared composite flexible graphite electrode was matched and assembled with a commercial carbon paper gas diffusion layer. A constant clamping force of 2.0 MPa was applied in the testing device to form a stable contact interface between the composite flexible graphite electrode and the gas diffusion layer. Subsequently, a constant current was applied, and the interfacial contact resistance was calculated by measuring the voltage drop generated at the interface between the composite flexible graphite electrode and the carbon paper. The influence of the resistance of the testing fixture and the substrate material itself was subtracted to obtain the true interfacial contact resistance value.

[0074] Hydrogen and helium permeability: The barrier properties of the composite flexible graphite plate to hydrogen and helium were tested using a differential pressure gas permeation apparatus. Before testing, the sample was processed to the specified dimensions and sealed in the permeation test chamber to ensure no gas leakage at the sample edges. During the test, hydrogen and helium were used as permeation media, and a constant pressure difference of 0.3 MPa was established on both sides of the sample, allowing the gas to permeate from the high-pressure side to the low-pressure side. By detecting the change in gas flow rate on the low-pressure side over time, the gas permeation rate per unit time, per unit area, and per unit pressure difference was calculated to obtain the hydrogen permeability and helium permeability.

[0075] Bending strength: The mechanical properties of the composite flexible graphite plate were evaluated using a three-point bending test conducted on a universal testing machine. Before the test, the specimen was processed to the specified dimensions, and the thickness and width of the specimen were measured. The specimen was placed horizontally between two support points, with the span between the support points controlled at 40 mm. A vertical load was applied through the loading head at a loading rate of 1 mm / min, and the loading was continued until the specimen fractured. The maximum load value was recorded, and the bending strength of the specimen was obtained according to the three-point bending calculation formula.

[0076] Corrosion current density: The electrochemical corrosion resistance of the composite flexible graphite electrode was tested using a three-electrode electrochemical workstation. The test system included a working electrode, a reference electrode, and an auxiliary electrode, with the composite flexible graphite electrode sample serving as the working electrode, a platinum sheet as the auxiliary electrode, and a saturated calomel electrode or a silver / silver chloride electrode as the reference electrode. Before testing, the sample surface was pretreated and immersed stably in a simulated proton exchange membrane fuel cell acidic corrosion environment composed of 80℃, 0.1mol / L sulfuric acid, and 2ppm hydrofluoric acid to stabilize the electrode interface. Subsequently, potentiodynamic polarization testing was used to obtain polarization curves at a set scan rate, and the corrosion potential and corrosion current density were fitted using the Tafel extrapolation method.

[0077] The performance test results are shown in Table 1.

[0078] Table 1 Performance Tests of Composite Flexible Graphite Plates: According to the data in Table 1, the carbon nanotube-reinforced composite flexible graphite electrode plates prepared in this application have good electrical and mechanical properties in Examples 1-4. Among them, the graphite electrode plates prepared in Examples 2 (adding lubricant) and 3 (preheating the composite graphite substrate) have better performance than those prepared in Example 1.

[0079] Further observation of Examples 1 and Comparative Examples 1-4 revealed that, compared to Comparative Example 6 (where raw material powders were directly mixed and then pressed into shape), the composite flexible graphite plates prepared in Comparative Example 1 (expanded graphite was not treated with an alkaline solution), Comparative Example 2 (carbon nanotubes were used directly without any treatment), Comparative Example 3, and Comparative Example 4 (without vacuum / pressure impregnation) all exhibited worse performance than the composite flexible graphite plates prepared in Example 1. Finally, observing Example 1 and Comparative Example 5, it can be seen that when the content of positively charged carbon nanotubes is too high, even if the same method is used to prepare the composite flexible graphite electrode, it will still affect the final performance of the composite flexible graphite electrode.

[0080] Other embodiments of this disclosure will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This application is intended to cover any variations, uses, or adaptations of this disclosure that follow the general principles of this disclosure and include common knowledge or customary techniques in the art not disclosed herein. The specification and examples are to be considered exemplary only, and the true scope and spirit of this disclosure are indicated by the following claims.

Claims

1. A method for preparing a carbon nanotube-reinforced composite flexible graphite electrode, characterized in that, The preparation method includes the following steps: S1. Expand the flake graphite to obtain expanded graphite, then immerse the expanded graphite in an alkaline solution and filter it to obtain negatively charged expanded graphite. S2. Carbon nanotubes are added to Fenton oxidation solution for oxidation treatment to obtain modified carbon nanotubes. Then, the modified carbon nanotubes are added to an aqueous solution containing amine salt for surface treatment and filtered to obtain positively charged carbon nanotubes. The Fenton oxidation solution contains ferrous ions and hydrogen peroxide. S3. Negatively charged expanded graphite and positively charged carbon nanotubes are added to an alcohol solution, ultrasonically dispersed, vacuum / pressure impregnated, filtered, washed with deionized water, and dried to obtain a composite powder. The composite powder is then rolled to obtain a composite graphite substrate. S4. Add the resin to an organic solvent, heat to dissolve, and obtain a resin solution. Then add the composite graphite substrate to the resin solution, vacuum, pressurize and impregnate, dry, hot press and cool to obtain a carbon nanotube-reinforced composite flexible graphite electrode.

2. The method for preparing a carbon nanotube-reinforced composite flexible graphite electrode according to claim 1, characterized in that, In step S1, the flake graphite is flake graphite with a purity of ≥99.98%, and the alkaline solution is an aqueous solution containing 1~2wt% alkaline substances, including at least one of ammonia, sodium hydroxide, sodium carbonate, and sodium bicarbonate.

3. The method for preparing a carbon nanotube-reinforced composite flexible graphite electrode according to claim 2, characterized in that, Step S1 includes: S1.1 Place the flake graphite in a reaction vessel, heat it to 850~950℃ for expansion treatment, cool it, and sieve it to obtain expanded graphite with a particle size of 100~500μm; S1.

2. Immerse expanded graphite in an alkaline solution, stir at 50~60℃ for 1.5~2.5h, filter to obtain negatively charged expanded graphite, wherein the mass ratio of expanded graphite to alkaline solution is 1:(8~10).

4. The method for preparing a carbon nanotube-reinforced composite flexible graphite electrode according to claim 1, characterized in that, In step S2, the length of the carbon nanotubes is 5-15 mm, the Fenton oxidation solution is an aqueous solution containing 0.01-0.05 mol / L sulfuric acid, 0.01-0.03 mol / L ferrous ions, and 2.4-3.6 mol / L hydrogen peroxide, and the amine salt includes at least one of ethylamine hydrochloride, ammonium chloride, propylamine hydrochloride, and ethylenediamine dihydrochloride.

5. The method for preparing a carbon nanotube-reinforced composite flexible graphite electrode according to claim 4, characterized in that, Step S2 includes: S2.1 Add carbon nanotubes to Fenton oxidation solution, stir and oxidize at 55~70℃ for 2~3h, filter and wash with deionized water until the pH of the filtrate is 6.5~7.5, and no red color appears when potassium thiocyanate solution is added to the filtrate, indicating that the washing is complete, and modified carbon nanotubes are obtained, wherein the mass ratio of carbon nanotubes to Fenton oxidation solution is 1:(20~30). S2.2 Add the modified carbon nanotubes to an aqueous solution containing amine salt, ultrasonically disperse at 30~40℃ for 60~120min, filter to obtain positively charged carbon nanotubes, wherein the mass ratio of modified carbon nanotubes to aqueous solution is 1:(8~10), and the concentration of amine salt in aqueous solution is 0.05~0.5mol / L.

6. The method for preparing a carbon nanotube-reinforced composite flexible graphite electrode according to claim 1, characterized in that, The alcohol solution in step S3 includes at least one of ethanol, isopropanol, and n-butanol.

7. The method for preparing a carbon nanotube-reinforced composite flexible graphite electrode according to claim 6, characterized in that, Step S3 includes: S3.1 Add negatively charged expanded graphite and positively charged carbon nanotubes to an alcohol solution and ultrasonically disperse for 30-50 min to obtain a suspension, wherein the mass ratio of negatively charged expanded graphite and positively charged carbon nanotubes to the alcohol solution is (94-96):(1-3):(500-700); S3.2 Place the suspension in a vacuum impregnation tank, first evacuate to below 10 kPa and maintain for 20-30 min, then pressurize to 0.8-1.3 MPa and maintain for 40-60 min, filter to obtain pre-composite powder; S3.

3. The pre-composite powder is added to a weak alkaline solution for neutralization and washed with deionized water until the conductivity of the filtrate is ≤2μS / cm to obtain a composite precipitate. The composite precipitate is then heated to 80~100℃ and dried for 2~3h to obtain a composite powder. The weak alkaline solution is an aqueous solution containing a weak alkaline substance with a mass concentration of 0.5~5wt%, and the weak alkaline substance includes at least one of ammonia, ammonium bicarbonate, and ammonium carbonate. S3.

4. The composite powder is fed into a double roller press for rolling to obtain a composite graphite substrate, wherein the thickness of the composite graphite substrate is 0.25~0.65mm.

8. The method for preparing a carbon nanotube-reinforced composite flexible graphite electrode according to claim 7, characterized in that, Step S3.1 also includes: S3.1 Add negatively charged expanded graphite and lubricant to an alcohol solution, stir and disperse to obtain a lubricating liquid, then add positively charged carbon nanotubes to the lubricating liquid and ultrasonically disperse for 30-50 minutes to obtain a suspension. The mass ratio of negatively charged expanded graphite, positively charged carbon nanotubes, lubricant and alcohol solution is (94-96):(1-3):(0.5-2):(500-700). The lubricant is polytetrafluoroethylene powder.

9. The method for preparing a carbon nanotube-reinforced composite flexible graphite electrode according to claim 1, characterized in that, In step S4, the resin is polyvinylidene fluoride resin and / or phenolic resin, and the organic solvent includes at least one of N-methylpyrrolidone, dimethylformamide, dimethylacetamide, dimethyl sulfoxide, tetrahydrofuran, and acetone.

10. The method for preparing a carbon nanotube-reinforced composite flexible graphite electrode according to claim 9, characterized in that, Step S4 includes: S4.1 Add the resin to an organic solvent and stir at 40~80℃ to dissolve it, thereby obtaining a resin solution, wherein the mass concentration of the resin in the resin solution is 17~21 wt%. S4.2 Add the composite graphite substrate to the resin solution, first evacuate to below 10 kPa and maintain for 20~30 min, then pressurize to 0.8~1.3 MPa and maintain for 40~60 min to remove and obtain the pre-fabricated graphite electrode plate, wherein the mass ratio of the composite graphite electrode plate to the resin solution is 1:(2~5). S4.

3. Heat the pre-made graphite electrode plate to 100~120℃ and dry it for 2~3 hours. Put it into the mold and keep it at 180~210℃ and 10~14MPa for 60~90 minutes. Cool, demold, and cut to obtain carbon nanotube reinforced composite flexible graphite electrode plate.

11. The method for preparing a carbon nanotube-reinforced composite flexible graphite electrode according to claim 10, characterized in that, Step S4.2 also includes: S4.2 Place the composite graphite substrate in a vacuum oven and preheat it at 60~80℃ for 20~40min to obtain a preheated substrate. Then transfer the preheated substrate to a resin solution at 40~80℃ for 1~3min, evacuate it to below 10kPa, maintain it for 20~30min, then pressurize it to 0.8~1.3MPa and maintain it for 40~60min to remove it and obtain a pre-fabricated graphite electrode plate. The mass ratio of the composite graphite electrode plate to the resin solution is 1:(2~5), and the temperature of the preheated substrate is higher than the temperature of the resin solution.

12. A carbon nanotube-reinforced composite flexible graphite electrode, characterized in that, The carbon nanotube-reinforced composite flexible graphite electrode plate is prepared by any one of the preparation methods of carbon nanotube-reinforced composite flexible graphite electrode plates according to claims 1-11.

13. The carbon nanotube-reinforced composite flexible graphite electrode plate according to claim 12, characterized in that, The carbon nanotube-reinforced composite flexible graphite electrode has a volumetric conductivity ≥292 S / cm and a surface resistivity ≤4.7 mΩ·cm. 2 Contact resistance ≤ 6.9 mΩ·cm 2 Flexural strength ≥ 76.3 MPa, hydrogen permeability ≤ 2.7 × 10⁻⁶ -9 cm 3 / (cm 2 (·s·Pa), helium permeability ≤2.1×10 -9 cm 3 / (cm 2 Corrosion current density ≤0.58 μA / cm² (·s·Pa). 2 .